Redescription of late-instar larva of Ptinella aptera (Guérin-Méneville, 1839) (Coleoptera: Ptiliidae) - Jałoszyński, Paweł (Zootaxa, 2014)
The late-instar larva of the featherwing beetle Ptinella aptera is redescribed. A coding system for chaetotaxic structures for ptiliid larvae is proposed and possible serial homology of setae across body segments is discussed. Previous, fragmentary and inaccurate descriptions of larval stages of P. aptera are discussed. The structures of immature P. aptera are compared with those of P. tenella and possible homologies and differences are indicated.